ANALISIS YURIDIS TERHADAP GUGATAN EKSEKUSI SITA JAMINAN AKIBAT WANPRESTASI ATAS PERJANJIAN KERJASAMA ANTARA PT. LAMINDO SAKTI DENGAN PT. PAKARTI TIRTOAGUNG (Studi Kasus Nomor: 808 PK/PDT/2018) - Agusta, Salma Haidar; Supanto, Adi; Kalyana, Lily (Lex Veritatis, 2022)
Humans are social creatures who cannot fulfil their own needs and to fulfil these needs. Humans need the help of others, in fulfilling their needs, namely by entering into an agreement, whether an agreement between an individual and an individual, an individual with a legal entity, or a legal entity with other legal entities. In a cooperation agreement it cannot be implemented by either party alone. The cooperation agreement includes the handover of part of the plaintiff's business (PT. Lamindo Sakti), while the defendant (PT. Pakarti Tirtoagung) carries out the operations of part of the plaintiff's business. Where the defendant agrees to enter into such cooperation by carrying out the obligations stated in the cooperation agreement. In its implementation, one of the parties that entered into the agreement was unable to carry out its obligations because of default and it resulted in a guarantee seizure of the promised goods. The main problem is how are the arrangements for the execution of collateral seizure as a result of default on a cooperation agreement and what is the judge's consideration in deciding cases. This research was conducted using the Normative Juridical Research Method. The theoretical basis refers to Article 1320 of the Civil Code and Article 1338 of the Civil Code. The conclusions are 1. Judge's consideration in making his decision was considered negligent by not paying attention to and considering the provisions contained in the agreement, so that the decision was detrimental to the Plaintiff, 2. The execution of collateral seizure in the case was not carried out, because the evidence was for confiscation. guarantee is not enough. The suggestions are 1. The judge should be more careful in handling a case so that he does not make a mistake in making a decision so as not to harm one of the parties, 2. If a guarantee seizure is required, it is hoped that the evidence to seize the guarantee is sufficient.